Análise de expressão dos genes de reparo da lesão de fita simples do DNA de trabalhadores rurais expostos à agrotóxicos - Costa, Marilia Braga (2017)
Population growth and the arising of the modern chemical industry have culminated in significant changes in agricultural productivity. The need of a increasingly food production has been linked to the use of chemicals to control and improve the development of agricultural products. In Ceará, specifically in region of Baixo Jaguaribe, the arrival of business agriculture has caused a re-ordering of agribusiness. Exposure to pesticides is often considered a major factor underlying increased risk of bone marrow disorders, including leukemia, myelodysplastic syndrome (MDS) and multiple myeloma in agricultural populations. Cumulative genetic damages are important events for the development of carcinogenesis and lack of efficacy in the DNA repair system is considered a major contributing factor.We evaluated the gene expression of targets related to DNA repair mechanisms, namely genes from the classes single strand break (SSB: CSA, CSB, XPA, XPC and XPG), using quantitative real time PCR from bone marrow samples of ninety farmers. Further, we also investigated karyotype of bone marrow cells by G-Band to confirm cytogenetic alterations. The participants were recruited from Limoeiro do Norte, a municipality in the northeastern of Brazil recognized by its intense agriculture activity, and divided into three groups according to their work segments: agriculture industry (AI), family farmers (FF) and organic farming (OF). There were significant differences across the three groups. AI individuals presented significantly lower transcript levels of XPG (p=0.004) and CSA (p=0.000) compared to the OF group. Similarly, FF presented significantly lower XPG (p=0.012) mRNA expression levels than OF. Among the farmers exposed to agrochemicals, we detected that those with more than 12 years of exposure showed an overall decrease in expression of XPC (p=0.001), XPG (p=0.010) and CSB (p=0.05) compared to those who had been exposed to less than 12 years. In addition, we detected significant correlations (p<0.05) between XPC and CSB (r=0.658), XPC and XPG (r=0.641), XPA and CSB (r=0.635), XPA and XPG (r=0.627), XPG and CSA (r=0.536), CSA and CSB (r=0.515), XPA and XPC (r=0.496), XPA and CSA (r=0.327). Whilst these correlations highlights the overall intrinsic relationship between single and double DNA strand breaks genes in bone marrow cells of these individuals, it is certainly notable the fact that the vast majority of the DNA repair genes investigated were downregulated in farmers exposed to pesticides, which vastly increments the risk of developing bone marrow cancers.